TEMPERATURE CHANGES IN CLOUD FOREST OF KHAO NAN NATIONAL PARK, SOUTHERN THAILAND DURING 2000 - 2015 - Anusa Suwanwong; Noodchanath Kongchouy (FORUM STATISTIKA DAN KOMPUTASI, 2015)
Khao-Nan National Park(KNNP) is a part of the Nakhon Si Thammarat mountain range, which is the one of the cloud forest southern Thailand. The characteristic of cloud forest is a plenty of flora especially epiphyte and the presence of clouds even in the dry season. The aim of this study was to investigate temperature pattern and variation at Khao Nan. We downloaded data, for land surface temperatures recorded by MODIS EARTH Satellites every eight days from 2000-2015 in square kilometers grid boxes covering Khao-Nan National Park, to investigate time series of temperature variation. The cubic spline modeling was used for fitting a pattern of LST among day time from satellite image at Khao-Nan National Park. Otherwise, we used GEE for parameter estimate. The result was shown the temperature has similar pattern and variation around Khao-Nan National Park during 2000-2015. Eventually, the conclusion is the temperature have changed during 2000-2005, 2006-2009 and 2010-2015 by using GEE.Key words : Temperature changes, cloud forest, Khao Nan National Park